Opportunities and Risks of Polish Presidency of the European Union from the Perspective of French Presidency Experience - Roznoch, Adam (Regional Barometer. Analyses & Prognoses, 2012)
The Polish presidency of the European Union has aroused a lot of ambitions and expectations from society, which sees opportunities to create and promote a positive image of Poland as a modern, dynamic country, engaged in the affairs of European integration and actively participating in solving current problems of the European community. Some are even convinced that the presidency will strengthen the position of Poland in the EU and worldwide. Looking from the perspective of the French Presidency experience, which has achieved many successes in this field, the author attempts to assess the opportunities and threats for the Polish presidency, bringing critical analysis of external factors, the priorities selected and the process of its preparation. Also presented are proposals for supporting the priorities of the Polish presidency, as well as some urgent problems to solve resulting from the challenges facing the European Union and Poland, today; including, in particular, the common agricultural policy, cohesion policy as well as territorial, economic and social competitiveness. The current Common Agricultural Policy has many imperfections and is a long way from the purposes it was originally intended.. The current direct payments to farmers in member countries are too varied and discriminate against farmers in the newly joined EU member states, especially in Poland, distorting the adopted principles of competitiveness. Consequently, it is an insufficiently implemented European cohesion policy. Even with the the absorption of considerable financial outlays, the outcome is the deepening of social, economic and territorial inequalities in particular regions and EU member states. The EU budget program for 2014–2020 assumes a substantial increase in expenditure on building competitiveness at the expense of cohesion among the regions of convergence, which will not encourage sustainable economic and social development in the EU, and especially in Poland. Poland does not duly use the EU subsidies for R & D, which, in this area, is a net contributor to the European budget. The consolidation of these trends, especially under conditions of the continuous overseas outflow of highly skilled human capital, is a huge threat to building a modern, innovative economy in Poland, disqualifying us for a long time in the rankings of European and global innovation. These and other threats to the Polish and European economy, in the context of a deepening monetary and economic crisis, should constitute the major challenges for the Polish presidency. Meanwhile, the program adopted by the presidency in this regard is too shallow and un-ambitious. Anxieties exist because the Polish presidency does not meet society’s expectations.